2010
DOI: 10.1002/hed.21592
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in laryngeal dysplasia: A systematic review

Abstract: Currently there is no good evidence for the use of biomarkers in predicting the future behavior of laryngeal dysplastic lesions. Only 3 studies showed statistically significant results. Better reporting of studies using the REMARK (REporting recommendations for tumor MARKer prognostic studies) consensus guidelines should help to improve this in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 40 publications
(95 reference statements)
0
24
0
Order By: Relevance
“…The concept of high‐grade SILs eliminates the problem of moderate dysplasia, which is a major source of interobserver variation in the dysplasia system. A similar improvement in interobserver agreement has been provided in the grading of oral dysplasia, through the introduction of a binary system …”
Section: Discussionmentioning
confidence: 81%
“…The concept of high‐grade SILs eliminates the problem of moderate dysplasia, which is a major source of interobserver variation in the dysplasia system. A similar improvement in interobserver agreement has been provided in the grading of oral dysplasia, through the introduction of a binary system …”
Section: Discussionmentioning
confidence: 81%
“…However, the five studies that analyzed this marker used different cut-offs to determine the percentage of p53 positive staining, which emphasizes the need for cautionary remarks on the value of immunohistochemistry as made above. Although a sensitivity analysis was performed for each of the cut-offs used, p53 was not found to significantly predict progression [45]. Only two of the seven studies included in our review that analyzed p53 showed a prognostic significance for this marker.…”
Section: Discussionmentioning
confidence: 85%
“…This problem has also been highlighted in another recent systematic review on this topic [45]. In that review, the authors only included 9 articles.…”
Section: Discussionmentioning
confidence: 94%
“…None of these were statistically significant either alone, or when pooled in a metaanalysis, with a risk ratio of 0.96 (95% CI=0.65, 1.42; P= 0.84). This lack of prognostic ability for p53 has also been demonstrated in laryngeal dysplasia [52]. In the same review, cathepsin L mRNA, MMP1/2 mRNA, p73, and LOH 8p all did not show a statistically significant predictive ability.…”
Section: Biomarkers With Potential Predictive/prognostic Abilitymentioning
confidence: 85%